A changing landscape. Issue 5 (September 2015) - Storey, Kate E.
<x xml:space="preserve">Abstract</x> Purpose of review Adolescents' dietary intake is an important determinant of health and well-being and is influenced by a complex interaction of environmental, social, psychological, and physiological factors. The complexity of the adolescent diet makes its assessment prone to error, which has prompted researchers and clinicians to turn to technology to reduce this error. Previous reviews have been conducted regarding the use of technology in dietary assessment for adults; however, there are no known reviews for adolescents. Therefore, the purpose of this review is to describe the practical considerations for web-based dietary assessment methods and to evaluate recent evidence on their validity and implications. Recent findings There are numerous web-based dietary assessment methods that are available, valid, and reliable for use in the adolescent population. Web-based methods include both native and web-based applications (or 'apps'), and have been developed for use as food records, 24-h dietary recalls, and food frequency questionnaires. Summary Web-based methods provide an efficient, cost-effective and practical solution to assess dietary intake; they are less burdensome to respondents and reduce errors and bias. Furthermore, adolescents are technologically savvy and often prefer the use of technology. Web-based methods should be considered when assessing adolescents' dietary intake.